(untitled) (International Seven Journal of Health Research, 2023)
OBJECTIVE: This article aims to report an extensive case of septic pelvic thrombophlebitis, a rare, severe, and challenging diagnostic condition. The clinical picture may range from mild to severe sepsis. Its diagnosis is of exclusion, but it can be complemented with imaging exams. CASE DESCRIPTION: We report a case of postpartum thrombophlebitis in the infrarenal portion of the inferior vena cava, external and internal common iliac veins, bilateral common femoral veins, as well as in the right ovarian vein, presenting with persistent fever and negative cultures. The patient showed significant clinical improvement after association of anticoagulation and antibiotic therapy. CONCLUSION: Septic pelvic thrombophlebitis is an important differential diagnosis for abdominal pain and fever in the postpartum period, but the absence of specific complementary tests makes its diagnosis challenging, which often leads to misdiagnosis of acute appendicitis, endometritis, pelvic inflammatory disease, pyelonephritis, nephrolithiasis, adnexal torsion, or pelvic abscess. The key to correct diagnosis is a high level of clinical suspicion, especially when there is resistance to broad-spectrum antibiotic therapy and remission after systemic anticoagulation. Given the large number of cesarean sections performed today and their correlation with septic pelvic thrombophlebitis, an increase in the number of cases should be accompanied by greater familiarity of health professionals with this complication, in order to avoid inadequate propaedeutics and conducts. In this context, the present case report documents the importance of investigating pelvic septic thrombosis in patients with fever in the puerperium and its differential diagnoses for early initiation of therapy to reduce morbidity and mortality.